Female sexual dysfunction after bariatric surgery in women with obesity: A systematic review and meta-analysis. (March 2022) - Loh, Huai H.; Shahar, Mohammad A.; Loh, Huai S.; Yee, Anne
Background and objective: Obesity is prevalent and has a negative impact on women's health, including sexual dysfunction. Recent review articles suggest improvement in Female Sexual Function Index (FSFI) and proportion of female sexual dysfunction (FSD) among women with obesity after bariatric surgery. Methods: We pooled data from 16 observational studies involving 953 women. The study outcomes were mean FSFI scores and proportion of FSD before and after bariatric surgery. We also sub-analyzed whether age and duration of follow-up affected these outcomes. Results: The mean age of the subjects was 39.4 ± 4.2 years. Body mass index (BMI) showed significant reduction postoperatively ( p < 0.0001). Bariatric surgery led to significant improvement in total FSFI score ( p = 0.0005), and all sexual domains except pain. Bariatric surgery reduced the odds of having FSD by 76% compared with those who did not undergo operation (OR 0.24, 95% CI = 0.17, 0.33, p < 0.0001). Our sub-analysis demonstrated a significant reduction in the proportion of FSD for patients <40 years of age. The improvement of total FSFI scores and reduction in proportion of FSD remained significant within the first 12 months after surgery. Univariate meta-regression showed that BMI was not a significant covariate for improvement of FSFI scores ( β = 0.395, p = 0.1, 95% CI = 0.884, 0.095). Conclusions: Bariatric surgery is shown to improve sexual function scores and prevalence of FSD. This is especially significant among women <40 years of age. This benefit remained significant within the first year after surgery. This appears to be an additional benefit for these patients.